Neck swelling with renal stone - Khan, MK; Taous, A; Sultana, SZ; Sharif, A; Hossain, MM; Mostafa, G; Hussain, MA; Azim, MA; Siddique, MA (Mymensingh Medical Journal, 2010)
Mymensingh Med J. 2010 Oct;19(4):622-6 The abstract of this article is available on the PubMed website